Service offshoring and its impacts on wages: An occupation-oriented analysis of Germany - Michael Frenkel; Ngoc Tuyet Ngo (The World Economy, 2023)
International trade in services has increased significantly in recent decades, mainly due to innovations in information and communication technology. This development has also increased the importance of service offshoring, as companies spread their production processes across several countries. This paper examines the intensity of offshoring of specific tasks of occupations, which in turn leads to higher imports, and explores the impact of such substitution on wages in the home economy. We use micro-level data from the Occupational Information Network and the Socio-Economic Panel in Germany and draw on the OECD's Input–Output Database. In total, we used data from about 62,000 person-years in 45 industries in Germany during 2014–2018. A particular focus of our study is on the interaction between service offshoring and the tradability as well as skill levels of workers. Our main findings suggest that service offshoring itself exerts downward pressure on workers' wages. This effect is amplified by the degree of tradability of the occupations.
Keywords: 330; international trade in services; microeconomic impacts; service offshoring; trade and labor market interactions